Il movimento torinese dei Consigli di Fabbrica e Il movimento comunista a Torino - Gramsci, Antonio (International Gramsci Journal, 2023)
From the original manuscript, held in the Comintern Archives, we publish for the first time in Italian the text of the article that Gramsci wrote for the November 1920 issue of the Comintern journal “Communist International” on the communist and council movements in Turin. For comparison purposes, we include in a parallel column the article as it was then published a few months later in “L’Ordine nuovo”, with modifications (presumably by Gramsci) made in this latter version, retranslated into Italian from the published German translation. Gramsci deals with the situation in Turin and the great strikes there during the First World War, the alliances formed between the working class and other social strata, and State repression of the workers’ armed insurrections. In the midst of these events, in May 1917, there was the first mass demonstration since Italy’s entry into the war, addressed by I. P. Goldenberg and A. N. Smirnov, delegates to the West of the Petrograd Soviet, and then both Men’ševiks. They were however greeted with cries in favour of Lenin and the Bol’ševiks, whose strategy in Petrograd was later – and independently – duplicated in Turin, with factory councils being formed on the initiative of the majority communist group in the Turin Socialist Party branch. The article closes with a criticism of the role of the reformist leadership of the Socialist Party and Unions, who ignored the role of the councils as the equivalent of “soviets”, the nuclei of a future democratic State.